2016
DOI: 10.1371/journal.pone.0156584
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Sensitivity of Honey Bees Is Differently Affected by Dietary Protein and a Neonicotinoid Pesticide

Abstract: Over a decade, declines in honey bee colonies have raised worldwide concerns. Several potentially contributing factors have been investigated, e.g. parasites, diseases, and pesticides. Neonicotinoid pesticides have received much attention due to their intensive use in crop protection, and their adverse effects on many levels of honey bee physiology led the European Union to ban these compounds. Due to their neuronal target, a receptor expressed throughout the insect nervous system, studies have focused mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 71 publications
4
15
0
Order By: Relevance
“…Our findings of an impact on learning performance from direct adult neonicotinoid exposure conforms with previous studies showing negative effects on learning in honeybees [68][69][70] and bumblebees [62]. However, our study design allowed us to compare responses between young and older adults receiving different chronic exposure histories.…”
Section: (A) Pesticide Exposure During Early Development Affected Ressupporting
confidence: 87%
“…Our findings of an impact on learning performance from direct adult neonicotinoid exposure conforms with previous studies showing negative effects on learning in honeybees [68][69][70] and bumblebees [62]. However, our study design allowed us to compare responses between young and older adults receiving different chronic exposure histories.…”
Section: (A) Pesticide Exposure During Early Development Affected Ressupporting
confidence: 87%
“…Lundin et al after analyzing 268 publications involving neonicotinoid researches, found that thiamethoxam was the second most studied component with 34%, in 73 studies. Recently, articles evaluating the exhibition of the thiamethoxam on pollinators have been pointed out as sublethal effects on behavior, locomotion, and memory, metabolism and immunity, reproduction, and synergistic effects of additional pesticides with neonicotinoids …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the P:C ratios achieved on our pollen treatments are broadly comparable to those in other studies on both honey bees and bumble bees provided with casein-based diets. For honey bees, these include P:C ratios ranging from 1:6.5 (Archer et al, 2014b;Démares et al, 2016) to 1:150 (Paoli et al, 2014). Although the study of Vaudo et al (2016) was focused on protein-to-lipid ratios, their data on consumption show P:C ratios of 1:69 and 1:85 in two bumblebee species.…”
Section: Discussionmentioning
confidence: 99%